Liver Metastasis–Directed Ablative Radiotherapy in Pancreatic Cancer Offers Prolonged Time Off Systemic Therapy in Selected Patients: Data From a Multi-institutional Retrospective Study. Issue 5 (May 2021) - Lee, Grace; Kim, Daniel W.; Oladeru, Oluwadamilola T.; Niemierko, Andrzej; Gergelis, Kimberly R.; Haddock, Michael G.; Toesca, Diego A. S.; Koong, Amanda J.; Owen, Dawn; Weekes, Colin; Hong, Theodore S.; Chang, Daniel T.; et al.
Abstract : Objectives: We evaluated the outcomes of metastatic pancreatic cancer (MPC) patients who underwent liver metastases (LMs)–directed ablative radiotherapy (RT) and sought to characterize patients with more favorable prognosis. Methods: A retrospective analysis of 76 MPC patients who underwent ablative RT (median dose, 50 Gy) to LM at 3 academic centers between 2008 and 2018 was performed. Endpoints were local control (LC), progression-free survival, and overall survival (OS) since RT. Results: Median follow-up was 10.9 months. Liver metastases were metachronous in 68%. Before RT, LM was responsive/stable on chemotherapy (CTX) in 36% whereas progressive in 43%. Median carbohydrate antigen 19-9 (CA 19-9) at RT was 334 U/mL. After RT, 32% had ≥6 months of CTX break. Twelve-month outcomes were: LC, 66%; progression-free survival, 7%; and OS, 38%. On multivariable analysis, Eastern Cooperative Oncology Group 2–3 (hazard ratio [HR], 13.49; P < 0.01), progressive LM on CTX (HR, 3.26; P < 0.01), and higher CA 19-9 (log10 scale; HR, 1.39; P < 0.01) at RT predicted worse OS. Conclusions: Ablative RT to LM in setting of MPC may offer LC of systemic disease and thus quality time off CTX. Selected patients with good performance status, stable/responsive LM on CTX, and lower CA 19-9 have more favorable prognosis.